Social buffering enhances extinction of conditioned fear responses in male rats - Mikami, Kaori; Kiyokawa, Yasushi; Takeuchi, Yukari; Mori, Yuji (Physiology & behavior, 2016)
In social species, the phenomenon in which the presence of conspecific animals mitigates stress responses is called social buffering. We previously reported that social buffering in male rats ameliorated behavioral fear responses, as well as hypothalamic-pituitary-adrenal axis activation, elicited by an auditory conditioned stimulus (CS). However, after social buffering, it is not clear whether rats exhibit fear responses when they are re-exposed to the same CS in the absence of another rat. In the present study, we addressed this issue using an experimental model of extinction. High stress levels during extinction training impaired extinction, suggesting that extinction is enhanced when stress levels during extinction training are low. Therefore, we hypothesized that rats that had received social buffering during extinction training would not show fear responses to a CS, even in the absence of another rat, because social buffering had enhanced the extinction of conditioned fear responses. To test this, we subjected male fear-conditioned rats to extinction training either alone or with a non-conditioned male rat. The subjects were then individually re-exposed to the CS in a recall test. When the subjects individually underwent extinction training, no responses were suppressed in the recall test. Conversely, when the subjects received social buffering during extinction training, freezing and Fos expression in the paraventricular nucleus of the hypothalamus and lateral amygdala were suppressed. Additionally, the effects of social buffering were absent when the recall test was conducted in a different context from the extinction training. The present results suggest that social buffering enhances extinction of conditioned fear responses. •Insufficient extinction training did not extinguish fear responses.•Social buffering during insufficient extinction training suppressed fear responses.•The effect of social buffering during extinction training was context specific.•We concluded that social buffering enhanced extinction of fear responses.